Provenancing ancient pigments: Lead isotope analyses of the copper compound of egyptian blue pigments from ancient mediterranean artefacts. (December 2017) - Rodler, Alexandra S.; Artioli, Gilberto; Klein, Sabine; Petschick, Rainer; Fink-Jensen, Peter; Brøns, Cecilie
Abstract: While the use of Egyptian blue (EB) as the earliest artificial pigment was common amongst ancient Mediterranean cultures throughout Egypt, Mesopotamia, Greece, and the Roman Empire, little is known about ancient production centres and the sources of raw materials. Variations in lead isotope (LI) ratios can be useful for fingerprinting the geological sources of copper metal, which has the potential to indicate local production or importation. This method is here applied to copper- and silica-rich EB pigments in order to investigate the provenance of the copper component. The investigated EB pigments were sampled from nine ancient artefacts of Egyptian, Etruscan, Canosan, and Roman origin (dating from between the 5th century BCE to the early 1st century CE) that are part of the archaeological collection of the Ny Carlsberg Glyptotek (NCG), Denmark. For the first time, copper isotope analysis was also applied to EB pigments to facilitate future studies of copper isotopes in such materials. Variations in copper isotopes hold the potential to complement lead isotope-based provenance considerations. The lead isotope data (LID) of the investigated EB pigments were compared to reference LID of copper minerals of European, Near and Middle Eastern, and North African ores that have been exploited at a time relevant for the studied EB pigments. In support of (i) a previously postulated scenario where the import of copper for producing EB dominated over the use of local resources (Shortland, 2006) and (ii) consistent with the preference for lead isotope-based exclusion of unlikely sources rather than the determination of certain provenance, copper ore deposits pertaining to Egyptian and Italian LI fields show no significant overlap with the LID of the studied EB pigments. Instead, we propose that copper sourced from various European (Aegean, Balkan, Iberian, Central European) deposits potentially supplied the production of the studied EB pigments. For example, (i) the studied Egyptian EB pigments show no overlap with Egyptian copper, but instead with Aegean sources; (ii) based on the highly variable copper provenance of the studied Etruscan EB pigments, we tentatively propose that this might argue for the importation of copper raw materials and a subsequent local production in Etruria, analogous to previously reported Etruscan glass production; (iii) we propose that Iberian copper was used for local EB production at a time when the known large-scale EB production facilities in the Bay of Naples were already active. While the testimony of ancient trade in EB is a difficult topic to unravel, the potential copper sources involved in producing EB pigments of the few investigated archaeological artefacts suggests that a few (EB) pigment workshops/production centres were highly actively trading raw materials and/or manufactured EB pigments with several different Mediterranean civilizations. Many EB pigment producing workshops and distribution sites may have existed throughout the Mediterranean facilitating a highly complex and diverse network of trade in this widely distributed ancient pigment. Highlights: We present the first copper isotope analyses of samples of Egyptian blue pigments. Lead isotope ratios of Egyptian blue pigments match geologically distinct regions. Trade in Aegean copper potentially supplied EB production at Memphis (1st c. BCE). Diverse copper origin is observed for EB of Etruscan, Canosan & Roman artefacts.